The relationship between childhood traumas, dissociation, and impulsivity in patients with borderline personality disorder comorbid with ADHD. Issue 4 (2nd October 2017) - Kulacaoglu, Filiz; Solmaz, Mustafa; Ardic, Ferhat Can; Akin, Ercan; Kose, Samet
ABSTRACT: Objective: Previous studies reported that there were significant associations between Attention-deficit/hyperactivity disorder (ADHD) and borderline personality disorder (BPD). In this study, we aimed to examine complex relationship between childhood trauma, impulsivity, dissociative symptoms, and the impact of ADHD on this relationship in a sample of patients with BPD. Methods: Our samples consisted of 165 BPD patients (128 female, 37 male) and 165 healthy subjects (128 female, 37 male) of similar age and gender. We administered the semi-structured socio-demographic data form, Adult Self-Report Scale, Barratt Impulsivity Scale (BIS-11), Childhood Trauma Questionnaire, and Dissociation Questionnaire. Results: The BPD group exhibited greater ADHD symptoms, impulsivity, childhood trauma, and dissociation compared to the healthy group. A statistically significant association was found between adult ADHD symptoms and impulsivity, childhood trauma, and dissociation scores. The logistic regression analysis indicated that gender, attentional and motor impulsiveness were the predictors of ADHD in BPD patients. Among these, gender and emotional neglect were the predictors of dissociation in BPD patients. Conclusion: Our results suggested a strong association between impulsivity, childhood trauma, dissociation, and ADHD symptoms in patients with BPD. The findings are mostly consistent with the literature. Clinicians should be aware of these symptoms among these populations to develop treatment strategies.